Development of a sputter-deposited nanocarbon thin film electrode for use as a biosensor. (January 2015) - Kamata, Tomoyuki; Kato, Dai; Niwa, Osamu
Abstract : We have developed nanocarbon film electrodes formed by an electron cyclotron resonance (ECR) sputtering method. The nanocarbon film contains a nano-crystalline sp 2 and sp 3 mixed bond structure with an atomically flat surface and has a wide potential window, relatively high electrochemical activity and a low background noise level similar to a boron-doped diamond electrode. Surface conditions such as hydrophilicity on the nanocarbon film electrode can be controlled by electrochemical treatments while maintaining the wide potential window and surface flatness, and, therefore, in measurements of various biomolecules including oxidatively damaged DNA and oligonucleotides, their adsorption onto the electrode surface is suppressed. For example, cytosine and methylated cytosine in oligonucleotides can be distinguished by square wave voltammetry. A carbon electrode with a thorn-like nanostructure could be fabricated by UV/ozone treatment using different etching rates depending on nanometer-order differences in the local sp 3 content of the nanocarbon film. This nanostructured surface was very effective in improving efficient direct electron transfer (DET) with enzymes such as bilirubin oxidase. Carbon film electrodes doped with metal nanoparticles have been also developed by co-sputtering metal and carbon. A Pt-nanoparticle-dispersed carbon electrode shows high electrochemical activity and stability for detecting hydrogen peroxide indicating that it is suitable for use as a biosensor. [TANSO 2014 (No. 264), 133–9.]